Constitutional review and fundamental rights: beware of the system's effects - Tusseau, Guillaume (2025)
The issue of constitutional revision, both in its practical applications and its very conceptualization, has experienced a resurgence in recent legal doctrine. This revival has coincided with a significant evolution in the field of fundamental rights, which are caught between being challenged by anti-liberal constitutionalism and expanding in the wake of environmental and digital constitutionalism. Starting from the idea that the Constitution is "the supreme law of the land", the dominant normative constitutionalism distinguishes between the organic and dogmatic parts of a constitution. While this distinction has the merit of clarity, it must be handled with caution. In fact, constitutional provisions are interdependent, as an analysis in terms of system effects reveals. Considering constitutional revision in one of its parts is bound to have an impact on the other, sometimes at the cost of jeopardizing the very objectives of the revision. Therefore, the constituent power, whose voluntarism is expressed mainly through constitutional revisions, must be attentive to these types of considerations, as must the citizens in whose name this power is exercised.